The effect of workload on burnout with role stress as a mediating variable in employees of pt. Trikayarasa jaya food - Nur Lailatus Solichah; Ayu Lucy Larassaty (Jurnal Mantik, 2024)
The purpose of the study was to determine the effect of workload on burnout with role stress as a mediating variable. Specific research objectives: 1) Knowing the effect of workload on burnout. 2) Knowing the effect of workload on role stress. 3) To determine the effect of role stress on burnout 4) To determine the effect of workload on burnout mediated by role stress variables. The urgency of this research can provide useful information for PT Trikayarasa Jaya Food to be able to overcome the workload pressure that occurs on employees in the production and stripping section. The type of data used in this research is quantitative data. The population in this study were the workers of PT Trikayarasa Jaya Food as many as 110 employees. The sampling technique in this study used purposive sampling. The sample used was employees of the production and stripping section totaling 70. The reason for sampling the production and stripping section is that the target is not met. This study uses questionnaire data collection methods and data collection instruments using a Likert scale. The data analysis technique in this study uses part analysis software used SmartPLS version 4.0. The results of this study are that there is an effect of workload on burnout, there is an effect of workload on role stress, there is an effect of role stress on burnout, there is an effect of role stress being able to mediate workload to burnout